Educação e gestão : o percurso histórico sobre a vida profissional de Sarita Baracat de Arruda no cenário educacional e político mato-grossense - Nascimento, Crissya Laura de Moraes (2020)
The research entitled Education and Management: The historical path about professional life of Sarita Baracat de Arruda in the educational and political context of Mato Grosso was developed in the master's course of the Graduate Program in Education at the Federal University of Mato Grosso, in the Research Line “School Organization, Training and Pedagogical Practices” and in the research group “Teaching and social memory, political action of subjects involved in and in the exercise of elective teaching political positions”. The main objective of the research is to record the professional career of Professor Sarita Baracat de Arruda (1930-2017), who dedicated her life to family, sport, education, politics and the municipality of Várzea Grande, she was the first woman to be elected councilor and, later, mayor of the city. In 1979, was the first woman to occupy the position of state deputy, after the division of the state of Mato Grosso and who, even after her retirement, remained fighting for education and for the development of your city. The methodology used for data collection and analysis was qualitative, as it allows us to use oral memory, through interviews and archived memory in official documents, newspapers, minutes and other documents, also bibliographic review by through the theoretical contribution in which it was anchored in the foundations referring to the methodology of Bogdan and Biklen (1994), as to the method, in Thompson (1992), Noronha (2011) and Stone (2011) and relative to the memory, in Le Goff (2003), Bosi (1994), Halbwachs (2006) and Ricoeur (2007). The research method was prosopography, also known as Career Analysis, in which it seeks to establish the study from uniform issues, such as birth and death, marriage and family, social origin, inherited economic position, place of residence, education, occupation and professional experience.